Membangun Kesadaran Ketahanan Lingkungan Pesisir Masyarakat Mundupesisir, Kabupaten Cirebon - Sri Wulandari; Rifal Pamuji; Saat Mubarrok (Lembaga Pengembangan Kinerja Dosen, 2025)
The POSEIDON 2025 program is a community service initiative focused on enhancing environmental resilience and improving the welfare of coastal communities in Kalijaga Hamlet. The program began with a series of surveys aimed at identifying environmental conditions, social dynamics, and the main issues faced by local residents. The survey results revealed rapid sedimentation, accumulated waste along the coastline, and seawater intrusion that rendered groundwater unfit for consumption. Based on these findings, several solution-oriented activities were designed, including the installation of a water filter in the mosque, seminars and socialization on the functions and conservation of mangroves, the planting of 100 mangrove seedlings, the restoration of the Community Hall with the addition of an environmental-themed reading corner, and a beach clean-up activity. The program was carried out over three days with the involvement of local residents, students, academics, and social organizations. The implementation results showed an increase in public awareness of the importance of protecting mangrove ecosystems and coastal cleanliness, improved access to clean water, and enhanced environmental literacy among children. This program demonstrates that interdisciplinary collaboration and active community participation play a vital role in achieving sustainable and resilient coastal development.